Desempenho cognitivo, indicadores comportamentais e afetivo-motivacionais na avaliação assistida de crianças com anemia falciforme - Lorencini, Grace Rangel Felizardo (2011)
The literature indicates that chronic disease represents an important risk factor for child development. Sickle cell anemia is the chronic disease of the greatest representation in our population. Its complications can bring multiple losses to the individual; among those, one may highlight lower cognitive performance. This study aimed to verify, through dynamic assessment, the performance of children with sickle cell anemia, considering both, cognitive and non-intellectual indicators. Twelve children aged between 8 and 10 years old, diagnosed with sickle cell disease, attending the Pediatric Hematology clinic of a public hospital in Vitoria, ES, participated in this study. The mothers of the children also participated in the study and for the characterization of the sample, the following instruments were applied: a) interview (adapted script for gathering information about the child's routine, course of illness and chronic pain experience, family interaction and resources available in environment; b) protocol to identify the family’s socioeconomic profile - Brazil Economic Classification Criterion, and c) assessment of social competence and behavior patterns through the Behavior Checklist, the Brazilian version of the Child Behavior Checklist - CBCL/6-18 years. For the dynamic assessment two tests with a distinct gradient of difficulty for their resolution were applied; the "Constraint-seeking questions game with several figures", in a computerized version (PBFD-comp), and the "Analogies Subtest" of the Cognitive Modifiability Battery (CMB), by David Tzuriel, a task of greater complexity. Also, specific instruments of this type of assessment were used: evaluation protocols of cognitive operations, behaviors, and affectivemotivational factors. The design of the study was the single-subject design, measuring intragroup variation and compared individual performance in each phase of the dynamic assessment. Regarding the main characteristics of the sample data, analysis of the CBCL indicated that most were classified as clinic for internalizing problems (83.3%), especially the subitem withdrawal (58.3%), the same pattern in the total score of social competence (83.3%). In the dynamic assessment, the group presented different profiles for each test. In the PBFD-comp children presented, in most cases, the profiles "high performance" and "gainer-maintainer". Cognitive operations, behaviors, and affectivemotivational factors were facilitators for the testing. Thus, the group benefited from the mediation offered keeping performance up in the transferring phase of the PBFD-comp. However, the same did not happen in the Analogies subtest, with low performance for the majority, translated into trouble keeping strategies to solve problems after discontinuation of assistance as well as to generalize the tips to more complex examples (transference phase - TRF). As for cognitive processing, there was a reduction of facilitating operations through the trial, mainly in the last phase, especially episodic perception and difficulty in integrating the information. The behavior and affective-motivational factors were, in general, facilitators, but showed a small decrease in the last phase (TRF). These data indicate that most children in relation to analogical reasoning require the systematization of new learning environments for optimal performance through structured and regulated mediation to the level of child development. The results corroborate the findings in the area that indicate dynamic assessment as a prescriptive method for identifying cognitive deficits, being an auxiliary tool in psychological diagnosis, and sustaining early intervention programs for people with sickle cell anemia. In addition to the cognitive variables, the importance of new studies that discuss the vulnerability of this population for the occurrence of emotional and behavioral problems, are emphasized.